Patient Preferences for Oral Anticoagulation Therapy in Atrial Fibrillation: A Systematic Literature Review - Wilke, Thomas; Bauer, Sabine; Mueller, Sabrina; Kohlmann, Thomas; Bauersachs, Rupert (The patient : patient-centered outcomes research, 2017)
Objectives Since the introduction of non-vitamin K antagonist (VKA) oral anticoagulants (NOACs), an additional treatment option, apart from VKAs, has become available for stroke prevention in patients with atrial fibrillation (AF). For various reasons, it is important to consider patients’ preferences regarding type of medication, particularly in view of the established relationship between preferences towards treatment, associated burden of treatment, and treatment adherence. This review aimed to systematically analyse the scientific literature assessing the preferences of AF patients with regard to long-term oral anticoagulant (OAC) treatment. Methods We searched the MEDLINE, Scopus and EMBASE databases (from 1980 to 2015), added records from reference lists of publications found, and conducted a systematic review based on all identified publications. Outcomes of interest included any quantitative information regarding the opinions or preferences of AF patients towards OAC treatment, ideally specified according to different clinical or convenience attributes describing different OAC treatment options. Results Overall, 27 publications describing the results of studies conducted in 12 different countries were included in our review. Among these, 16 studies analysed patient preferences towards OACs in general. These studies predominantly assessed which benefits (mainly lower stroke risk) AF patients would require to tolerate harms (mainly higher bleeding risk) associated with an OAC. Most studies showed that patients were willing to accept higher bleeding risks if a certain threshold in stroke risk reduction could be reached. Nevertheless, most of the publications also showed that the preferences of AF patients towards OACs may differ from the perspective of clinical guidelines or the perspective of physicians. The remaining 11 studies included in our review assessed the preferences of AF patients towards specific OAC medication options, namely NOACs versus VKAs. Our review showed that AF patients prefer easy-to-administer treatments, such as treatments that are applied once daily without any food/drug interactions and without the need for bridging and frequent blood controls. Conclusion Stroke risk reduction and a moderate increase in the risk of bleeding are the most important attributes for an AF patient when deciding whether they are for or against OAC treatment. If different anticoagulation options have similar clinical characteristics, convenience attributes matter to patients. In this review, AF patients favour attribute levels that describe NOAC treatment.